A Bioeconomic Solution for Replacing Chemical Fertilizers by Organic Processes for Atmospheric Nitrogen Fixation in Soil - Gabriela Loredana Dinulescu; Valentina Ofelia Robescu; Florin Radu; Gabriel Croitoru; Valentin Radu (Amfiteatru Economic)
Large-scale use of nitrogen-based chemical fertilizers, specific to intensive agriculture, has undesirable effects consisting of soil degradation and atmospheric loading with carbon dioxide. Good practice illustrates, however, that sustainable agriculture can be achieved by substituting as much as possible chemically synthesized nitrogen with biologically fixed nitrogen. This research is part of a study cycle that aims to use the natural symbiotic fixation models to bring into the soil and plants as much as possible atmospheric nitrogen, non-polluting, antioxidant and generator of humus and durability. We had work with a pea culture, seated in a rotation of 4 years the type pea, wheat-rape, maize, and we watched at three parameters of the symbiotic fixation between peas with species Rhizobium leguminosarum. The experiments were carried out in two locations in southern Romania (Burnas Plain - on the Plateau of Alexandria, and in the Southern Plain - Modelu, Calarasi) and the results were: • in dynamics the nodosities begin to form at 22-24 days after sowing, their number increases accentuated until the 37 days of life, after which it decreases slightly until the 70th day. The maximum number of nodosities on roots reaches a number of 57-58 per plant. The life of a nodosity is not longer than 10 days; • the weight of dry nodosities is on the peak of biological activity higher at Modelu (5.8 g/m2) at 38 days after sowing, and less in Alexandria (4.1 g/m2) at 37 days after sowing (Figure no. 2 in-text); • starting from the weight of the nodosites and using their transformation coefficient in the N (nitrogen) active substance (which is 4.6), and using the functional analysis of the correlations and integral calculations, the dynamics of nitrogen accumulation in the form of a high precision polynomial function (order 14) was obtained (figure no. 3 in-text), which tells us that: the highest amount of nitrogen is obtained on day 41 after sowing in the amount of 6.52 Kg N active substance/ha. Cumulative calculation obtained through the integral function the total and average quantity obtained for the two locations in 2016 – 2017 was about 116 kg N/ha (1).